Exploring Spirituality and Cognitive Styles as a Predictor of Suicidal Ideation in Urban Population - Tanya Aneja; Rita Kumar (International Journal of Behavioral Sciences, 2025)
Suicidal ideation, or the thought of suicide, is a complicated and multi-dimensional issue of public health that effects individuals globally at a individual level, in families and in society at large. It is one of the main causes of death in the world. Beliefs, practices and experiences pertaining to the transcendence, sacred or divine, are all included in the broad category of spirituality. In cognitive psychology, the term "cognitive style" or "thinking style" refers to how people think, perceive, and retain information.. The purpose of the study is to use regression and correlation to assess both spirituality as well as cognitive styles as predictors of suicidal thoughts. Using a sample of N=301 (aged 20-35 years), Data was gathered using the positive and negative, suicide, inventory, Cognitive styles, inventory and spirituality scale. The results indicate that spirituality levels—self-discovery, eco-awareness, and relationships—had a significant positive correlation with positive suicidal ideation and a significant negative correlation with negative suicidal ideation, whereas cognitive styles—the system, a category, and the intuitive category—had no significant correlation with either positive or negative suicidal ideation. Additionally, a 0.2% prediction level between cognitive styles and negative suicidal ideation was discovered with a 99.99% accuracy level and a 23% prediction level between spirituality and negative suicidal ideation. Lastly, a 73% prediction level for negative suicidal ideation was revealed when spirituality and cognitive styles were combined. Consequently, it was determined that cognitive styles and spirituality or predictive factors for suicidal thoughts.
Keywords: Cognitive Styles; Negative Suicidal Ideation; Positive Suicidal Ideation; Suicidal Ideation; spirituality